Judicial policy lines in the criminal sanctioning of environmental offenses: an empirical study - Billiet, Carole
We analyze judicial policy lines concerning criminal environmental sanctioning using a unique European dataset of individual criminal cases, including case-specific information on offenses and offenders. We investigate policy choices made by criminal judges in lower courts as well as the relevant court of appeal. The sanctioning policy of judges proofs to be varied as well as consistent. Judges decide to postpone convictions for cases they deem less important. They carefully balance effective and suspended sanctions, in general using them as substitutes, but in specific cases opting to use them cumulatively. Overall, judges in lower courts balance environmental and classic criminal law and aim at protecting individuals and their possessions as well as the environment.